2017
DOI: 10.1177/1321103x17706735
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the rationale for group music activities for parents and young children: Parents’ and practitioners’ perspectives

Abstract: Children’s Centres are widespread in England and comprise multi-professional staff teams seeking to work with families with children aged 0–5 years. Although parent–child group music sessions appear frequently in Children’s Centre activity programmes, the rationale for their inclusion remains unclear. This article presents the results from phase two of an exploratory mixed-methods study which investigated the role of and rationale for parent–child (0–3 years) group music making activities in Children’s Centres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…Our results imply that participation in regular group music lessons could be a reasonable means for promoting children’s levels of sociability, particularly for very young children whose social behaviors are malleable ( Brownell, 2013 ). Having lessons 2–4 times per month is probably not too much music activity for children and their parents; thus, such effects of sociability also bear out very young children’s parents’ expectations for their sociability in group music activity ( Pitt and Hargreaves, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results imply that participation in regular group music lessons could be a reasonable means for promoting children’s levels of sociability, particularly for very young children whose social behaviors are malleable ( Brownell, 2013 ). Having lessons 2–4 times per month is probably not too much music activity for children and their parents; thus, such effects of sociability also bear out very young children’s parents’ expectations for their sociability in group music activity ( Pitt and Hargreaves, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The article is based on a pilot study funded by Cambridge University (Burnard et al, 2018) which set out to investigate the role that musical and sonic activities in museums can play within their local communities: museums represent a potentially rich space for families with young children in disadvantaged communities to access, and hence enjoy, multiple benefits. Specifically, museums hold the potential to engage such families in early years music practice, which has been shown to offer myriad cognitive, social, emotional, and educational benefits (Osgood et al, 2013a; Pitt and Hargreaves, 2016, 2017). Furthermore, perhaps more broadly, ‘a permeating presence of self-initiated music making in childhood suggests that it may serve a purpose in human development, that is, to provide the child with the cultural tools necessary to make sense of their world’ (Custodero et al, 2016: 56).…”
Section: Introductionmentioning
confidence: 99%
“…Parents in this study identified that music was a fun way to learn and practise social and emotional skills. This is supported by Pitt & Hargreaves research that reported parents perceived attending a music group provided children an important opportunity to socialise in a group (Pitt & Hargreaves, 2017).…”
Section: Subtheme 23: Music To Support the Development Of Emotional mentioning
confidence: 66%
“…MELP attendance was observed to support language development in the home for all of the children through the use of songs and games taken directly from the MELP and used throughout the day, as documented in written and video diaries. Pitt and Hargreaves (2017) reported that the benefits to speech and language skills were considered to be the most beneficial reason for children attending a parent-child music program in the UK. Similarly, Blackburn (2017) reported outcomes of a survey conducted with 125 parents in the UK that identified key benefits of participating in a music program.…”
Section: Subtheme 22: Music To Support Language Development and Commmentioning
confidence: 99%
See 1 more Smart Citation